A comparison of clinical characteristics and outcome in pyogenic liver abscess patients with and without diabetes mellitus: A case-control study - Haitao Sun; Yuxian Yang; Eric A Klomparens; Dong Zhao (Wolters Kluwer Medknow Publications, 2019)
Background: Pyogenic liver abscess (PLA) is a relatively rare and potentially life-threatening disease. The incidence of PLA has been increasing steadily over the past few decades. PLA is relatively common in patients with diabetes mellitus (DM). Although multiple studies have explored the relationship between PLA and DM, it remains controversial, and the evidence comes primarily from case reports. Because of this, more studies are necessary to compare the characteristics of PLA patients with and without DM to explore the relationship between PLA and DM. Materials and Methods: A total of 115 PLA patients admitted in Beijing Luhe Hospital from December 2012 to August 2017 were divided into two groups based on the presence of DM (the DM group and the non-DM group) for the comparison of clinical characteristics and outcomes of patients. Chi-square, Fisher's exact, and t-tests were used to analyze the differences between the two groups. Results: Of 115 patients included, 50.4% of patients had DM. The DM group had a lower prevalence of abdominal pain (28% vs. 51%, P = 0.011) and pain to palpation (48% vs. 67%, P = 0.046). Moreover, the DM group had a higher prevalence of misdiagnosis (45% vs. 16%, P = 0.001) and poor outcomes (9% vs. 0%, P = 0.03). Conclusions: We found that patients with DM may have less typical symptoms of PLA than those without DM, which may explain the higher prevalence of misdiagnosis of PLA in patients with DM. Moreover, patients with DM have worse outcomes than those without DM.